A cloudy fuzzy economic order quantity model for imperfect-quality items with allowable proportionate discounts - Sujit Kumar De; Gour Chandra Mahata (Journal of Industrial Engineering International, 2019)
In the traditional economic order quantity/economic production quantity model, most of the items considered are of perfect type. But this situation rarely takes place in practice. Thus, in this paper, an economic order quantity model with imperfect-quality items is developed. 100%100%screening process is performed, and the items of imperfect quality are sold as a single batch. A proportionate rate of discount for the items of imperfect quality has also been studied. Moreover, a case study has been incorporated to comprehend the model. To nullify the issues of non-random uncertainties of demand rate in business scenario, cloudy fuzzy method has been utilized here. Numerical study reveals that cloud model along with its new defuzzification methods can give maximum profit of the model all the time instead of deterministic ones. Finally, sensitivity analysis and graphical illustrations are made to justify the novelty of the model.
Keywords: 650; EOQ; Screening cost; Imperfect quality; Cloudy fuzzy number; New defuzzifcation method; Optimization